2008
DOI: 10.1152/ajprenal.90301.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal in the urethra are cGMP-mediated targets of nitrergic neurotransmission

Abstract: While interstitial cells of Cajal (ICC) in the urethra respond to nitric oxide (NO) donors by increasing cGMP, it remains unclear whether urethral ICC are functionally innervated by nitrergic nerves. We have addressed this issue in the rat and sheep urethra, where cGMP production and relaxation were compared in preparations subjected to electrical field stimulation (EFS; 2 Hz, 4 min) of nitrergic nerves or to exogenous S-nitroso-L-cysteine (SNC; 0.1 mM, 4 min). Upon EFS, cGMP immunoreactivity (cGMP-ir) was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…In some of the cells, PDE2 was found co-localized with vimentin, a specific feature of ICs and neurons, thereby confirming earlier findings describing immunolabeling for ICs in cardiac tissue and the urogenital tract (Figure 3c). [13][14][15][16][17] Staining specific for PDE11A (dual-substrate PDE) was observed in single nerve trunks located in the clitoral stroma (Figure 1f). In contrast, no labeling indicating PDE2 or PDE5 was observed in nerve fibers or nerve endings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some of the cells, PDE2 was found co-localized with vimentin, a specific feature of ICs and neurons, thereby confirming earlier findings describing immunolabeling for ICs in cardiac tissue and the urogenital tract (Figure 3c). [13][14][15][16][17] Staining specific for PDE11A (dual-substrate PDE) was observed in single nerve trunks located in the clitoral stroma (Figure 1f). In contrast, no labeling indicating PDE2 or PDE5 was observed in nerve fibers or nerve endings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…23 26,27 ICs have also been identified by immunoreactivity for the transmembrane receptor protein c-kit, the gap junction protein connexin 43 or vimentin, an intermediate filament subunit of mesenchymal cells. 13,14,16 Usually, ICs can be found adjacent to their target cells, such as smooth muscle cells, epithelial cells or nerve endings. 28 It has been suggested that ICs may have a pivotal role as so-called pacemakers and mediators of neurotransmission in the bladder, urethra and penile erectile tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 ICs in rat urethra are also reported that they act as effectors of nerve-released NO, responding to NO donors by increasing intracellular cGMP. 14 In the present study, we isolated ICs from guinea pig corpus cavernosum and purified them by fluorescence-activated cell sorting, which were recognized to have sufficiently high numbers and purity to permit detailed molecular analyses. 30 The result of western blot revealed coexpression of sGCa1, sGCb1 and c-kit protein in the fresh purified ICs.…”
Section: Discussionmentioning
confidence: 97%
“…6,[9][10][11] Recent morphological and functional evidence from various organs suggests that ICC and ICs might act as the primary targets for nerve-released NO to have a important role in NO-dependent signal transduction and smooth muscle relaxation. [12][13][14] ICs have been identified by their immunoreactivity to the kit receptor in the corporal tissue from man and several animals. [15][16][17] As dispersed corporal SMCs are able to generate spontaneous electrical activity by opening Ca 2 þ -activated Cl À channels, which is primarily initiated by spontaneous Ca 2 þ store-dependent membrane depolarization, 18,19 the role of ICs in corporal tissues as the primary electrical pacemaker has been questioned; they may serve as intermediaries in the transmission of nerve signals to SMCs or have other functional roles.…”
Section: Introductionmentioning
confidence: 99%